2020
DOI: 10.1016/j.ecolind.2020.106616
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hot spots of aquatic plant biomass in a large floodplain river catchment in the Australian wet-dry tropics

Abstract: Conservation planning processes and wetland management require spatial estimations of aquatic habitats to support the maintenance of aquatic biodiversity. However, physical access to several wetlands and freshwater habits can be restricted due to difficult topography and technological limitations associated with ground-based observations. In addition to these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…These aquatic plants can provide food for crabs and eventually form a stable food chain [45]. At the same time, the growth of aquatic plants can also take away excess nutrients in the water body, increase the nitrification and denitrification of organic waste by microorganisms, and stabilize the reservoir ecosystem [57,58]. In addition, aquatic plants can also increase the three-dimensional living space protection of the creatures and improve the biodiversity of the reservoir [58].…”
Section: Discussionmentioning
confidence: 99%
“…These aquatic plants can provide food for crabs and eventually form a stable food chain [45]. At the same time, the growth of aquatic plants can also take away excess nutrients in the water body, increase the nitrification and denitrification of organic waste by microorganisms, and stabilize the reservoir ecosystem [57,58]. In addition, aquatic plants can also increase the three-dimensional living space protection of the creatures and improve the biodiversity of the reservoir [58].…”
Section: Discussionmentioning
confidence: 99%
“…We found that MNDWI and the OSAVI indices were the best predictors of water and the presence of rooted aquatic plants. Both indices have been previously adopted for floodplains studies; for example, MNDWI was used to predict the presence of water [68,69] and OSAVI was used to predict vegetation biomass [69]. Identifying the best set of predictors and the thresholds for classification allows for the prediction of key productive habitats across larger areas, which can be used as inputs for further analysis, e.g., for periphyton abundance studies [20] and for turbidity [25].…”
Section: Discussionmentioning
confidence: 99%
“…The wet season (December to March) may result in extensive flooding of the catchment for days to weeks (Ndehedehe et al, 2020). During the dry season (April to November), the combination of high evapotranspiration, and no flow through the catchment, results in a fall in river height, and the cessation of river flow.…”
Section: Study Sitementioning
confidence: 99%